Thermal annealing to influence the vapor sensing behavior of co-continuous poly(lactic acid)/polystyrene/multiwalled carbon nanotube composites - Yilong Li; Jürgen Pionteck; Petra Pötschke; Brigitte Voit (Materials & Design, 2020)
With the main purpose of being used as vapor leakage detector, the volatile organic compound (VOC) vapor sensing properties of conductive polymer blend composites were studied. Poly(lactic acid)/polystyrene/multi-walled carbon nanotube (PLA/PS/MWCNT) based conductive polymer composites (CPCs) in which the polymer components exhibit different interactions with the vapors, were prepared by melt mixing. CPCs with a blend composition of 50/50 wt% resulted in the finest co-continuous structure and selective MWCNT localization in PLA. Therefore, these composites were selected for sensor tests. Thermal annealing was applied aiming to maintain the blend structure but improving the sensing reversibility of CPC sensors towards high vapor concentrations. Different sensing protocols were applied using acetone (good solvent for PS and PLA) and cyclohexane (good solvent for PS but poor solvent for PLA) vapors. Increasing acetone vapor concentration resulted in increased relative resistance change (Rrel) of CPCs. Saturated cyclohexane vapor resulted in lower response than nearly saturated acetone vapor. The thermal annealing at 150 °C did not change the blend morphology but increased the PLA crystallinity, making the CPC sensors more resistant to vapor stimulation, resulting in lower Rrel but better reversibility after vapor exposure. Keywords: Poly(lactic acid), Carbon nanotubes, Polymer blend, Electrical resistivity, Annealing, Vapor sensor